2011
DOI: 10.1155/2011/190731
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Nitrogen Availability of Heat-Dried Biosolids

Abstract: As heat-dried biosolids become more widely produced and marketed, it is important to improve estimates of N availability from these materials. Objectives were to compare plant-available N among three different heat-dried biosolids and determine if current guidelines were adequate for estimating application rates. Heat-dried biosolids were surface applied to tall fescue (Festuca arundinacea Schreb.) in Washington State, USA, and forage yield and N uptake measured for two growing seasons following application. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Based on previous research on N availability from dewatered and heat-dried biosolids [10] we estimated plant-available N of both biosolids sources as 25% of total N under the conditions of this study and used that estimate for our field application rates ( Table 2). In a more recent study of heat-dried biosolids conducted in western Washington State in 2007-2009, Cogger et al [11] reported much greater N availability from Soundgro, and we adjusted our estimate of available N applied from Soundgro to 50% of total N. The ramifications of this change are discussed later. Biosolids were surface applied at or up to two weeks prior to planting at each location.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous research on N availability from dewatered and heat-dried biosolids [10] we estimated plant-available N of both biosolids sources as 25% of total N under the conditions of this study and used that estimate for our field application rates ( Table 2). In a more recent study of heat-dried biosolids conducted in western Washington State in 2007-2009, Cogger et al [11] reported much greater N availability from Soundgro, and we adjusted our estimate of available N applied from Soundgro to 50% of total N. The ramifications of this change are discussed later. Biosolids were surface applied at or up to two weeks prior to planting at each location.…”
Section: Methodsmentioning
confidence: 99%
“…Initial attempts to target biosolids agronomic rates to match the intermediate (56 or 90 kg N ha −1 ) or high (112 or 180 kg N ha −1 ) N fertilizer rates were apparently unsuccessful based on N availability calculations as a fraction of total N in the materials (Table 2). These availability indices were developed from studies in which biosolids were applied in the fallow period of a crop-fallow rotation and were incorporated with tillage [3,18] or broadcast on the surface for a perennial forage crop [11]. In the present study, biosolids were applied shortly before planting and left on the surface.…”
Section: Wheat Response To Inorganic N Fertilizer and Biosolidsmentioning
confidence: 99%
“…Milorganite (Milwaukee Organic Nitrogen) is prepared from heat-dried microbes that digested municipal and industrial wastes from Milwaukee Metropolitan Sewerage District (MMSD) (Archer 2007 ). Milorganite can be used as a soil amendment and fertilizer for the production of diverse crops (Cogger et al 2011 ). According to the label on the packaging materials, the nitrogen contents of milorganite, chicken manure, and cow manure is 6%, 3%, and 0.5%, respectively, which were validated in our lab by analyzing samples from these organic amendments using inductive coupled plasma optical emission spectrometer (Agilent ICP-5100) working with both radial and axial view and C, H, N, and S content using elementar vario Macro tube.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the level of nitrogen, the most limiting plant nutrient, in organic amendments is lower than in conventional inorganic fertilizers (Rigby and Smith 2014 ). Moreover, the nitrogen in organic fertilizers and soil amendments is slowly released to plants (Cogger et al 2011 ). Therefore, to meet nitrogen requirements of crops, organic amendments are applied at higher rates (Cogger et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation